PERANAN PENGKOTBAH DALAM IBADAT SABDA - Batu, Johannes Lumban (SEPAKAT-Jurnal Pastoral Kateketik, 2017)
Sermons are an integral part of liturgical action and are included in theâLiturgy of The Wordâ. The very close relationship between the Word of Godand the Church that takes place in its doctrine, life, and worship becomes thesource of the Church to preserve and carry on, both itself and its full faithfrom generation to generation (cf. DV 8). This statement makes the Churchaware of preaching as part of the Churchâs own preaching. Preaching is anattempt to develop Christian faith and life by explaining the newly read textsof Scripture.